Чужое дело: роман / Ольга Славина - Славина Ольга (Женский детектив, 2008)
Экземпляры: ф.13 (20171017) / Инвентарный номер: 57746 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 47 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44